A Hybrid Masonry and Steel Mirror-Type Vault with Lunettes: Survey and Structural Analysis. Issue 4 (20th April 2020) - Condoleo, Paola; Gobbo, Antonia; Taliercio, Alberto
ABSTRACT: The structural analysis of a mirror-type vault, consisting of a single- or double-curvature perimeter and a nearly flat part, is carried out. The vault is similar to a number of hybrid iron (or steel) and masonry vaults built between the late 19th century and the early 20th century to span large halls. The numerical analyses were preceded by an accurate geometrical survey and mechanical tests aimed at evaluating the properties of the materials. Thermography allowed the complex brick pattern of the vault to be detected. The influence of rib-walls (frenelli) and the material anisotropy on the stress and deformation of the vault is discussed. Eventually, attention is focused on one of the segmental vaults in the central part of the structure: it is found that the stress can be safely estimated by assuming its boundary to be fixed.